Three‐Dimensional Cathode Constructed through Confined‐Growth of FeP Nanocrystals in Ordered Mesoporous Carbon Film Coated on Carbon Cloth for Efficient Hydrogen Production. Issue 16 (28th June 2018) - Liu, Zhipeng; Gao, Zhichao; Luo, Feng; Yuan, Shisheng; Wang, Kaiwen; Li, Nan; Li, Xiaotian
Abstract: Efficient, stable, and affordable electrocatalysts are essential for large‐scale hydrogen generation through water electrolysis. Nanosized catalyst particles integrated with a conductive current collector are highly desirable candidates yet quite challenging to synthesize. In this study, we prepared a self‐supported electrode constructed with FeP nanocrystals confined in the pores of ordered mesoporous carbon‐coated carbon cloth (FeP@OMC/CC) for efficient hydrogen evolution reaction (HER). The synergistic effect of ultrafine FeP nanocrystals, ordered mesoporous configuration and highly conductive carbon fiber framework endowed the self‐supported electrode with enriched active sites, accelerated charge and mass transport and strong mechanical stability. Consequently, the as‐synthesized FeP@OMC/CC electrode exhibited remarkable HER performance with a low overpotential (10 mA cm −2 at an overpotential of 51 mV), small Tafel slope (39 mV dec −1 ), and superior structural and electrochemical stability (over 20 h under an overpotential of 70 mV), which is one of the highest electrocatalytic performance observed among all nonprecious materials. Abstract : Delicate but powerful : A delicate self‐supported electrode constructed by FeP nanocrystals encapsulated in ordered mesoporous carbon modified carbon cloth is employed for efficient hydrogen evolution in water electrolysis which exhibits a low overpotential of 51 mV at 10 mA cm −2, small Tafel slope of 39 mV dec −1 and excellent stability.